A Case of Congenital Central Hypothyroidism Caused by a Novel Variant (Gln1255Ter) in IGSF1 Gene - Doğa Türkkahraman; Nimet Karataş Torun; Nadide Cemre Randa (Galenos Yayincilik, 2021)
Loss-of-function mutations in the immunoglobulin superfamily, member 1 (IGSF1) gene cause X-linked central hypothyroidism, and therefore its mutation affects mainly males. Central hypothyroidism in males is the hallmark of the disorder, however some patients additionally present with hypoprolactinemia, transient and partial growth hormone deficiency, early/normal timing of testicular enlargement but delayed testosterone rise in puberty, and adult macro-orchidism. Here, we report a boy with congenital central hypothyroidism caused by a novel variant in the IGSF1 gene. In our patient, early testicular enlargement but delayed testosterone rise with central hypothyroidism and hypoprolactinemia were the most important clues for diagnosis. In genetic analysis, we identified a novel, hemizygous nonsense c.3763 C>T (G1n1255Ter) variant in IGSF1 gene. To our knowledge, this is the first reported case of IGSF1 deficiency from Turkey.